Mortality and causes of death of traumatic spinal cord injury in Finland - Johansson, Elina; Koskinen, Eerika; Helminen, Mika; Vainionpää, Aki; Luoto, Teemu M (Spinal cord, 2025)
Prospective cohort study. To study the mortality rates of TSCI patients compared to matched controls and to examine possible TSCI-related mortality risk factors and causes of death. Oulu and Tampere University Hospital, Finland. All consecutive patients with a new TSCI were included in a prospective study (n = 344, 2012-16). All patients were followed until death or the end of 2019. Patients were compared to a control group formed by randomly choosing gender, age, municipality, and calendar time-matched controls (5 controls/TSCI patient). Standardized mortality ratios (SMR) were calculated using general population mortality rates. Mortality information was extracted from the Statistics of Finland (Helsinki, Finland). TSCI patients had an increased mortality (SMR = 2.9) compared with the Finnish population. During the observation period, 26% of TSCI patients and 12% of the matched controls died. Of the TSCI patient deaths, 51% occurred within the first two years postinjury. Increased age, severity of TSCI (as per International SCI Core Data Set) and fall were related to mortality (p < 0.05). The two most common etiologies of death were: circulatory (30%), and pulmonary diseases (28%). Pneumonia was the single most frequent disease leading to death among TSCI patients. During the first years after injury, the mortality of the patients with TSCI is double compared to the controls. Most deaths occur within two years postinjury. Elderly patients with more severe fall-related injury have the highest mortality risk. Circulatory diseases and pulmonary diseases, especially pneumonia, are the foremost causes of death after TSCI.